Faktor-Faktor Yang Berpengaruh Terhadap Audit Delay Perusahaan Sektor Perdagangan Yang Terdaftar Di Bei Periode 2007-2009 - . Divianto (SOSIALITA, 2011)
The study aims to determine the factors that influence audit delay trade sector companies listed on the Stock Exchange 2007-2009 period. The factors studied are delay is estimated to affect audit firm size, leverage level and quality of KAP. The population in this study is the trading company's financial statements listed on the Stock Exchange from 2007-2009. Sampling technique with elected sampling (non-probability sampling) by purposive sampling. Of the 24 companies that are trading at the Indonesian Stock Exchange from the year 2007-2009, there were only 21 companies that meet the characteristics of the samples that have been determined. The results of this study is the first hypothesis which states that the size of the company, significantly influence audit delay is acceptable. Significantly influence the regression coefficients for 1.270 and 0.005 the significance of the direction of positive relationships. The second hypothesis of this study which states that the level of corporate leverage significant effect on audit delay is acceptable. Significantly influence the regression coefficients for 1.099 and 0.011 the significance of the direction of positive relationships. The third hypothesis of this study which states that the level of corporate leverage significant effect on audit delay is unacceptable. Significantly influence the regression coefficients for 0.318 and 0.399 the significance of the direction of positive relationships. While the dominant variables is firm size that affect the audit delay can be accepted with the same value of the regression coefficients with their respective 1.270 values of significance (p = 0.005).